2012
DOI: 10.1080/02786826.2011.645955
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft Instrument for Comprehensive Characterization of Aerosol Optical Properties, Part 2: Black and Brown Carbon Absorption and Absorption Enhancement Measured with Photo Acoustic Spectroscopy

Abstract: This paper describes the design and performance of a photoacoustic aerosol absorption spectrometer (PAS) built for operation on a research aircraft platform. The PAS instrument is capable of measuring dry absorption at 659 nm, 532 nm, and 404 nm, and absorption enhancement due to coatings at 532 nm and 404 nm. The measurement accuracy for all channels is < = 10% and inflight 1 Hz sensitivities lie within the range of 0.5-1.5 Mm −1 . PAS measurements of calibrated absorbing aerosol samples are shown to be consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
196
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 145 publications
(207 citation statements)
references
References 53 publications
11
196
0
Order By: Relevance
“…Photoacoustic spectroscopy (PAS) has become a popular technique for measuring absorption of light by atmospheric aerosols for PAS (Lack et al, 2006(Lack et al, , 2012, recent works exploring its validity have come to contradictory conclusions: Bluvshtein et al (2017) saw a discrepancy between ozone calibrations and particle-based calibrations, while Davies et al (2018) found this not to be the case. Concurrent to these publications, we have been exploring the use of ozone as a PAS calibrant for multipass, multi-wavelength, aerosol photoacoustic spectrometers; our observations are presented here to add to the discussion on the topic.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Photoacoustic spectroscopy (PAS) has become a popular technique for measuring absorption of light by atmospheric aerosols for PAS (Lack et al, 2006(Lack et al, , 2012, recent works exploring its validity have come to contradictory conclusions: Bluvshtein et al (2017) saw a discrepancy between ozone calibrations and particle-based calibrations, while Davies et al (2018) found this not to be the case. Concurrent to these publications, we have been exploring the use of ozone as a PAS calibrant for multipass, multi-wavelength, aerosol photoacoustic spectrometers; our observations are presented here to add to the discussion on the topic.…”
Section: Introductionmentioning
confidence: 96%
“…By using multiple concentrations (or sizes, in the case of aerosols), a linear regression of s vs. b abs can be performed from which the slope, m, can be determined. Examples of calibrants include aerosol particles such as flame-generated soot (Arnott et al, 2000) and gas-phase absorbers such as ozone (Lack et al, 2006(Lack et al, , 2012 or nitrogen 20 dioxide (Arnott et al, 2000;Lewis et al, 2008;Cross et al, 2010). Although ozone absorbs weakly in the UV-A and violet regions of the spectrum and is difficult to measure at those wavelengths, it has been employed for field calibrations because it can be easily generated using a UV lamp or corona discharge.…”
mentioning
confidence: 99%
“…at 365 and 405 nm, and contribute approximately 10 % at midvisible wavelengths, e.g. at 532 nm (Bahadur et al, 2012;Lack et al, 2012b;Washenfelder et al, 2015;Nakayama et al, 2014). During an agricultural waste burning event, BrC aerosol could contribute more than 65 % of light absorption at 370 nm and 15 % at a mid-wavelength (Favez et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Cavity ring-down extinction: the b ext measurements at 405 and 532 nm were made using the UC Davis (UCD) twowavelength cavity ring-down photoacoustic spectrometer (CRD-PAS) instrument (Langridge et al, 2011;Lack et al, 2012). Full details of these measurements are available in Cappa et al (2016) and Atkinson et al (2015).…”
Section: Instruments Used At the T0 Site (American Rivermentioning
confidence: 99%